2011
DOI: 10.1371/journal.pone.0019351
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Exposure Decreases CREB Binding Protein Expression and Histone Acetylation in the Developing Cerebellum

Abstract: BackgroundFetal alcohol exposure affects 1 in 100 children making it the leading cause of mental retardation in the US. It has long been known that alcohol affects cerebellum development and function. However, the underlying molecular mechanism is unclear.Methodology/Principal FindingsWe demonstrate that CREB binding protein (CBP) is widely expressed in granule and Purkinje neurons of the developing cerebellar cortex of naïve rats. We also show that exposure to ethanol during the 3rd trimester-equivalent of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 68 publications
7
63
0
1
Order By: Relevance
“…Similarly, alcohol exposure during the early postnatal period in rats resulted in a marked reduction of CBP levels and histone acetylation in the developing cerebellum [70] . In ddY mice species, chronic ethanol vapor treatment showed an increase in both global and gene-specific histone acetylation in the ventral midbrain during withdrawal that hiked around 10 h post-alcohol exposure [71] . Additionally, probable communications among various factors may result in different time courses for alcohol-induced alterations, as histone acetylation measured 24 h after the last repeated alcohol injections was raised in some brain areas (e.g., frontal cortex and nucleus accumbens), decreased in others (e.g., striatum), and unaffected in still other regions of the brain (e.g., hippocampus) [71] .…”
Section: Impact Of Alcohol On Histone Acetylation/ Deacetylationmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, alcohol exposure during the early postnatal period in rats resulted in a marked reduction of CBP levels and histone acetylation in the developing cerebellum [70] . In ddY mice species, chronic ethanol vapor treatment showed an increase in both global and gene-specific histone acetylation in the ventral midbrain during withdrawal that hiked around 10 h post-alcohol exposure [71] . Additionally, probable communications among various factors may result in different time courses for alcohol-induced alterations, as histone acetylation measured 24 h after the last repeated alcohol injections was raised in some brain areas (e.g., frontal cortex and nucleus accumbens), decreased in others (e.g., striatum), and unaffected in still other regions of the brain (e.g., hippocampus) [71] .…”
Section: Impact Of Alcohol On Histone Acetylation/ Deacetylationmentioning
confidence: 98%
“…In ddY mice species, chronic ethanol vapor treatment showed an increase in both global and gene-specific histone acetylation in the ventral midbrain during withdrawal that hiked around 10 h post-alcohol exposure [71] . Additionally, probable communications among various factors may result in different time courses for alcohol-induced alterations, as histone acetylation measured 24 h after the last repeated alcohol injections was raised in some brain areas (e.g., frontal cortex and nucleus accumbens), decreased in others (e.g., striatum), and unaffected in still other regions of the brain (e.g., hippocampus) [71] . Further activation of different genes is coupled with acetylation of different residues of H3 and H4 at various time intervals [72] .…”
Section: Impact Of Alcohol On Histone Acetylation/ Deacetylationmentioning
confidence: 98%
“…Pandey et al (2008) found that acute alcohol exposure was associated with a decrease in total HDAC activity and increases in acetylation of histones H3 and H4, levels of CREB, and NPY expression in total cell lysates of amygdala [124]. Then the team of Guo et al (2011) documented that acetylated H4 levels were high at postnatal day 2 and decreased gradually until day 12 in naive animals [126]. On the other hand, ethanol exposure significantly reduced acetylated H4 levels in the cerebellum of the rats during postnatal days 2-10 and this was as a consequence of a downregulated HAT [126].…”
Section: Alcohol Effects On Brain Development: Epigenetic Insightsmentioning
confidence: 99%
“…We recently identified alterations in the cerebellar expression of a protein-cyclic adenosine monophosphate response element-binding protein (CREB) binding protein (CBP)-a histone acetyltransferase that acts as a cofactor for CREB and other transcription factors and plays a key role in synaptic plasticity (Guo et al, 2011). Histone acetylation typically results in chromatin relaxation, facilitating gene transcription.…”
Section: Epidemiology and Clinical Management Of Visceral Obesitymentioning
confidence: 99%